Immune system dysfunction and inflammation in aging Shank3b mutant mice, a model of autism spectrum disorder - Cerilli, Enrica; Dall’O, Ginevra Matilde; Chelini, Gabriele; Catena, Benedetta; Weinberger, Birgit; Bozzi, Yuri; Pangrazzi, Luca (Frontiers in Immunology, 2024)
Autism spectrum disorder (ASD) is a heterogeneous group of neurodevelopmental conditions characterized by deficits in social interaction/communication and restrictive/repetitive behaviors. Recent studies highlight the role of immune system dysfunction and inflammation in ASD pathophysiology. Indeed, elevated levels of proinflammatory cytokines were described in the brain and peripheral blood of ASD individuals. Despite this, how this pro-inflammatory profile evolves with aging and whether it may be associated with behavioral deficits is unknown. In this work, we explored the impact of aging on motor behavior and inflammation using Shank3b mutant mice, a model for syndromic ASD. Using RT-qPCR and flow cytometry, we examined the expression of key pro-inflammatory molecules in the cerebellum, bone marrow, spleen, and peripheral blood, comparing adult and old Shank3b +/+ , Shank3b +/-, and Shank3b -/-mice. Our findings revealed genotype-and age-related differences in inflammation and motor behavior, with Shank3b -/-mice exhibiting accelerated aging and motor impairments. Correlations between pro-inflammatory molecules and behavioral deficits suggest that a link may be present between systemic inflammation and ASD-related behaviors, underscoring the potential role of agerelated inflammation ("inflammaging") in exacerbating ASD symptoms.